Swedish Healthcare Reimagined: The Hospital at Home Approach - Ekholm, Albin; Rorsman, Johannes (My University, 2024)
This thesis explores the "Hospital at Home" (HaH) model as a strategic innovation to address the increasing pressures on the Swedish healthcare system due to aging populations and demographic shifts. The HaH model, which provides advanced medical care in patients' homes, offers a potential solution to enhance healthcare efficiency and quality. This study evaluates the feasibility and structure of integrating the HaH model into Sweden's unique healthcare landscape, focusing on patient selection, technological integration, and regulatory challenges. A literature review, case studies, and interviews with healthcare professionals, decision-makers, and medtech industry representatives provide the basis for the research. The findings indicate that HaH can reduce healthcare costs, improve patient outcomes, and enhance patient satisfaction. However, successful implementation in Sweden requires systemic flexibility, technological readiness, and collaborative efforts across regional healthcare entities. This research contributes to the debate on innovative healthcare delivery models and provides practical insights for policymakers and healthcare providers.
Keywords: Hospital at Home; Swedish healthcare; healthcare innovation; patient care; healthcare efficiency; patient satisfaction